Prognostic role of mesangial IgM deposition in IgA nephropathy: a long-term cohort study - Gabriel Stefan; Simona Stancu; Adrian Zugravu; George Terinte-Balcan (Renal Failure)
Background The clinical significance of mesangial immunoglobulin (Ig) M deposition in IgA nephropathy (IgAN) has been less explored and remains a topic of debate. Therefore, our study aimed to investigate the prognostic value of mesangial IgM deposition in a long-term follow-up cohort of IgAN patients.Methods A unicentric retrospective study was conducted on 93 consecutive IgAN patients (median age 41 years, 68% male, eGFR 48.7 mL/min, proteinuria 1.1 g/g) from 2010 to 2015. They were followed until end-stage kidney disease (ESKD), death, or until the end of the study in January 2021, with a median follow-up of 7 years. An independent pathologist evaluated the IgM immunofluorescence pattern, Oxford MEST-C score, and transmission electron microscopy (TEM) lesions following a comprehensive protocol.Results In our cohort, 70% had mesangial IgM-positive deposits, while 30% were IgM-negative. Both groups were similar in age, sex, prevalence of arterial hypertension, Charlson comorbidity scores, kidney function (eGFR and proteinuria), pathology findings (Oxford MEST-C score, IgG and C3 immune deposition), and TEM analysis. Treatment with RASI and immunosuppression, and death rates were also comparable. However, 37% of IgM-positive patients progressed to ESKD, significantly higher than the 11% in the IgM-negative group. Univariate and multivariate Cox proportional hazards regression analyses identified lower eGFR, higher Oxford MEST-C score, and mesangial IgM deposits as independent factors associated with shorter kidney survival.Conclusions Our study highlights mesangial IgM deposition as a potential risk factor for ESKD in patients with advanced IgAN, laying a foundation for further research in this area.